Hydrodynamic effects on oyster aquaculture systems: a review. (8th July 2018) - Campbell, Matthew D.; Hall, Steven G.
Abstract: Hydrodynamics (i.e. interactions of fluid motion with solid bodies) affect oyster aquaculture within every phase of farming. Although it has many direct and indirect implications to the success of any particular aquaculture endeavour, hydrodynamics is the least understood of environmental factors affecting oyster growth. As the industry continues to mature, it is imperative that the influence of hydrodynamics on oyster aquaculture is thoroughly understood. Hydrodynamics also interacts with other environmental factors, such as salinity, temperature, turbidity, food supply and oxygen, which affect the health and growth of oysters through mixing and transport. Proper siting and management of aquaculture requires a comprehensive understanding of the hydrodynamics involved and its impact on the culture of oysters. Unfortunately, literature is inconsistent on oyster feeding and growth response to the influence of hydrodynamics. Feeding and growth limiting velocities are reported that range from 1 to above 22 cm s −1 . This is in contrast with thriving oyster reefs in a natural setting that exist and thrive above 15 cm s −1 . Upweller systems have reported bulk velocities that range from 0.5 to 7.1 cm s −1 . In practice, higher current velocities are desirable because they increase delivery of food to the oysters, improve water quality, and enhance dispersal of biodeposits. This paper summarizes the findings of those studies in regard to hydrodynamics and provides suggestions for future work.